Psychometric properties of a Turkish version of the oral health impact profile-14 - Balcı, Nur; Alkan, Neşe; Gürgan, Cem Abdülkadir (Wolters Kluwer Medknow Publications, 2017)
Objectives: The purpose of this study was to analyze and evaluate a Turkish translation of the oral health impact profile-14 (OHIP-14) in a Turkish population to provide an objective standard for future studies. Methods: This cross-sectional research study consisted of three independent studies. Data were collected utilizing a personal interview and a review of periodontal records. This study was performed on 1205 subjects who were visiting for routine medical check-ups. The OHIP-14 was administered to measure oral health related to the quality of life, along with a questionnaire addressing demographic information, such as age, gender, and education. Results: The reliability coefficient (Cronbach's alpha) of the Turkish version OHIP-14-TR (OHIP-14-TR) was reported to be nearly perfect in all 3 parts of our study (alpha 1: 0.82; alpha 2: 0.76; alpha 3: 0.91); additionally, values were greater than the recommended 0.70 threshold. Spearman's correlation coefficients showed that both OHIP scores significantly correlated with periodontal parameters, serving as proof of convergent validity (P < 0.01, P < 0.001). The principal component analysis with varimax rotation revealed seven factors. The OHIP-14-TR was more than 95% comprehensible. Conclusion: The OHIP-14-TR is a reliable, valid, and comprehensible scale for measuring oral health-related quality of life in the Turkish population.
WOS: 000391533800004
PubMed ID: 27958241
Keywords: Oral Health; Quality of Life; Reliability; Validity